(untitled) (Bangladesh Journal of Agricultural Research, 2014)
Mungbean is one of the most important pulse crops in Bangladesh. The demand of mungbean is very high due to its good taste. To date, different national institutes released 14 improve mungbean varieties with complete package of technologies and disseminated them to the farmers. But, the farm level adoption of mungbean varieties, their economics, and farmers efficiencies are not well known to the researchers and policy planners. Therefore, the study assessed the farm level adoption of mungbean technologies, technical efficiency of mungbean growers, and find out constraints to its higher production. Data were collected from 283 randomly selected mungbean farmers from Jessore, Kushtia, and Barisal districts during March-April 2009. The highly adopted mungbean varieties were BARI Mung-3, 4 and 5. Technologies, such as ploughing, weeding, and seed rate occupied higher level of adoption. Sowing time and insect-pest control were medium level and irrigation was lower level adoption. In case of chemical fertilizer, urea secured higher level of adoption followed by TSP and MoP. The yield and net return of mungbean was 1196 kg and Tk. 15678 per hectare, respectively. The benefit cost ratio was 1.69 and 2.47 on full cost and cash cost basis, respectively. About 67% farmers achieved more than 90% technical efficiency level. Twenty eight percent farmers technical efficiency level, between 81-90% and the rest 5% farmers technical efficiency level was less than 80%. Diseases and pest infestation, lack of good quality seed, lack of knowledge about improved technologies were the major constraints to mungbean cultivation. Government should provide hand-on training and distribute quality seed to the farmers for increasing the area of mungbean cultivation. DOI: http://dx.doi.org/10.3329/bjar.v39i1.20149 Bangladesh J. Agril. Res. 39(1): 113-125, March 2014